Abnormalities in the Metabolism of Fatty Acids and Triacylglycerols in the Liver of the Goto‐Kakizaki Rat: A Model for Non‐Obese Type 2 Diabetes. Issue 8 (2nd July 2016) - Karahashi, Minako; Hirata‐Hanta, Yuko; Kawabata, Kohei; Tsutsumi, Daisuke; Kametani, Misaki; Takamatsu, Nanako; Sakamoto, Takeshi; Yamazaki, Tohru; Asano, Satoshi; Mitsumoto, Atsushi; Kawashima, Yoichi; Kudo, Naomi
Abstract: The Goto‐Kakizaki (GK) rat is widely used as an animal model for spontaneous‐onset type 2 diabetes without obesity; nevertheless, little information is available on the metabolism of fatty acids and triacylglycerols (TAG) in their livers. We investigated the mechanisms underlying the alterations in the metabolism of fatty acids and TAG in their livers, in comparison with Zucker ( fa / fa ) rats, which are obese and insulin resistant. Lipid profiles, the expression of genes for enzymes and proteins related to the metabolism of fatty acid and TAG, de novo synthesis of fatty acids and TAG in vivo, fatty acid synthase activity in vitro, fatty acid oxidation in liver slices, and very‐low‐density‐lipoprotein (VLDL)‐TAG secretion in vivo were estimated. Our results revealed that (1) the TAG accumulation was moderate, (2) the de novo fatty acid synthesis was increased by upregulation of fatty acid synthase in a post‐transcriptional manner, (3) fatty acid oxidation was also augmented through the induction of carnitine palmitoyltransferase 1a, and (4) the secretion rate of VLDL‐TAG remained unchanged in the livers of GK rats. These results suggest that, despite the fact that GK rats exhibit non‐obese type 2 diabetes, the upregulation of de novo lipogenesis is largely compensated by the upregulation of fatty acid oxidation, resulting in only moderate increase in TAG accumulation in the liver.